Community dynamics drive punctuated engraftment of the fecal microbiome following transplantation using freeze-dried, encapsulated fecal microbiota. (4th May 2017) - Staley, Christopher; Vaughn, Byron P.; Graiziger, Carolyn T.; Singroy, Stephanie; Hamilton, Matthew J.; Yao, Dan; Chen, Chi; Khoruts, Alexander; Sadowsky, Michael J.
ABSTRACT: Fecal microbiota transplantation (FMT) is a highly effective treatment of recurrent and recalcitrant Clostridium difficile infection (rCDI). In a recent study oral-delivery of encapsulated, freeze-dried donor material, resulted in comparable rates of cure to colonoscopic approaches. Here we characterize shifts in the fecal bacterial community structure of patients treated for rCDI using encapsulated donor material. Prior to FMT, patient fecal samples showed declines in diversity and abundance of Firmicutes and Bacteroidetes, with concurrent increases in members of the Proteobacteria, specifically Enterobacteriaceae . Moreover, patients who experienced recurrence of CDI within the 2-month clinical follow-up had greater abundances of Enterobacteriaceae and did not show resolution of dysbioses. Despite resolution of rCDI following oral-administration of encapsulated fecal microbiota, community composition was slow to return to a normal donor-like assemblage. Post-FMT taxa within the Firmicutes showed rapid increases in relative abundance and did not vary significantly over time. Conversely, Bacteroidetes taxa only showed significant increases in abundance after one month post-FMT, corresponding to significant increases in the community attributable to the donors. Changes in the associations among dominant OTUs were observed at days, weeks, and months post-FMT, suggesting shifts in community dynamics may be related to the timing of increases in abundance of specific taxa. Administration of encapsulated, freeze-dried, fecal microbiota to rCDI patients resulted in restoration of bacterial diversity and resolution of dysbiosis. However, shifts in the fecal microbiome were incremental rather than immediate, and may be driven by changes in community dynamics reflecting changes in the host environment.